Identification of Berenil Target Sites in Plasmid pBR322 - Valenzuela, MS (Int J Bioorganic Chem Mol Biol, 2017)
Berenil, a minor groove DNA binding molecule, has been extensively used in veterinary medicine. Modeling studies have suggested that berenil binds to A/T rich regions on the DNA and the product of this interaction causes the formation of crosslinks between opposite DNA strands. These crosslinks could potentially inhibit fundamental biological processes including transcription and DNA replication. We had previously used the pBR322 genome as a model system to investigate the role of A/T sequences on berenil activity. We reported that the insertion of poly(dA)poly(dT) sequences into the pBR322 genome causes replication inhibition of the recombinant plasmids when cultures were exposed to berenil. However, we noticed that even in the absence of these sequences the parental plasmid replication was also inhibited, albeit less than the recombinants. This observation led us to the present study were we attempted to identify the location of natural berenil target sites in the pBR322 genome. Through a combination of deletion analysis, recombinant DNA and a replication assay we uncovered a 378 bp DNA fragment that has all the hallmarks of a berenil target site. A recombinant plasmid lacking this region is more refractive to the drug than the parental plasmid, and another variant containing and extra copy of this region increases the susceptibility of the plasmid towards berenil. The 378 bp region is about 60% A/T rich and contains about 21 potential berenil binding sites.